ANALYSIS OF REGIONAL ECONOMIC GROWTH IN THE SMALL AND MEDIUM ENTERPRISE SECTOR IN SUNGAI PAUH PUSAKA VILLAGE - Andi Tarlis; Yulina Astuti; Krisniawati (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Business activities are hard work to improve people's lives. Basically, the diverse needs of the community encourage people with various business activities which are then expected to be able to meet these needs. For economic livelihoods, people need to identify potential and opportunities in the surrounding environment that will be used as business opportunities. The research method used is field research or using a qualitative approach. The results of the study are: a) The economic growth of business actors in Sungai Pauh Pusaka Village, West Langsa District, Langsa City with the many developments of business actors emerging in the village has an impact on the economic growth of the community, considering that the activities of micro, small and medium enterprises can change the economy for a community, but in 2020 economic growth experienced a decline of 87% caused by Covid-19, b) The main problem faced by business actors in Sungai Pauh Pusaka Village is the problem of decreasing turnover of their merchandise, this is caused by the Covid-19 Pandemic which has not ended.